A MODEL OF COMMUNICATIVE TEACHING AND LEARNING OF ENGLISH VOCABULARY THROUGH INTERACTIVE ACTIVITIES - Sri Endang Kusmaryati (Universitas Muria Kudus, 2018)
Teaching English vocabulary is very important, and it is more than just presenting and introducing new vocabulary to the students. Knowing words is not only memorizing them, but the students need to understand the meaning of the word in context and how the words are used. This can be achieved through correct vocabulary instruction which should involve vocabulary selection, word knowledge and techniques. This article aims to describe how to design a model of communivative teaching and learning of English vocabulary through interactive activities.